Keberadaan Awig-Awig dalam Mengatasi Aksi Tindak Pidana Ringan di Desa Marga Kabupaten Tabanan, Bali - I Nengah Wijana; Deli Bunga Saravistha (AL-DALIL: Jurnal Ilmu Sosial, Politik, dan Hukum, 2023)
The existence of customary law itself is recognized in Indonesian positive law, namely in the 1945 Constitution of the Republic of Indonesia Article 18 B paragraph (2). Customary law has its own uniqueness according to the custom in which the law lives, so it is not uncommon for there to be differences between customary law in one area and another. Several regions in Indonesia that have strong cultural characteristics still practice customary laws that have been enforced for a long time, such as Aceh which still uses Islamic law and Bali which also uses customary law guidelines to resolve problems that arise in society known as Awig-Awig. Awig-awig comes from the word "wig" which means damaged while "awig" means not damaged or good. So Awig-Awig is interpreted as something that becomes good. Like positive law, the awig-awig desa pakraman which guides the life of village krama certainly prohibits criminal acts and sanctions (pamidanda) are regulated in it. The rise of violence between youths is very troubling among the community members, as reported by the media where high school aged children were caught planning brawls which they called the "Sarong War". This action was successfully arrested by the police. This disturbing action is not only dangerous and requires special attention because it is related to the mentalistic development of the nation's generation, so it is very interesting to study, especially regarding the role of village awig-awig who are closest and directly touch the community.